Classification of high and low level of PM10 concentrations in Klang and Shah Alam, Malaysia / Hasfazilah Ahmat ...[et al.] - Ahmat, Hasfazilah; Musa, Nor Syahida; Nazamid, Nurhanina; Zaharin, Nursyahirah Amirah (Penerbit UiTM, 2019)
Particulate matter (PM) comprises of a complex mixture of small solid or liquid particles of organic and inorganic elements that floats freely in air. PM10 is defined as a particulate matter with an aerodynamic diameter of 10 m or less. The main objective of this paper is to classify the level of PM10 in selected locations in Peninsular Malaysia using discriminant analysis. Two important components considered in this study, namely; the meteorological factors and pollutant factors. The meteorological factors comprise of wind speed, wind direction, humidity and temperature while pollutant factors consist of Carbon Monoxide (CO), Sulphur Dioxide (SO2), Nitrogen Dioxide (NO2) and Ozone (O3). The classification of high or low level of PM10 concentrations was based on the Malaysia Ambient Air Quality Guideline (MAAQG). The findings indicated that the classification equation differs from location to location due to different levels of PM10 concentrations, location of monitoring stations and factors affecting air pollution in that location. The simulation data also verified that the classification of PM10 concentration was almost similar to the real condition that occurred in Klang in October 2015.